The Use of Monopoly Media in Social Students to Improve Motivation and Learning Outcomes of Elementary School Students - Mulyawati, Yuli; Gani, Resyi A (International Conference on Elementary Education, 2020)
This study used the Classroom Action Research method which was aimed to know and describe the improving of motivation and learning outcomes through the use of monopolistic media in social studies subjects. The research subjects were 28th grade students of Katulampa 1 Public Elementary School, Bogor Timur subdistrict, Bogor City, totaling 28 students. Data collection techniques through observation, interviews and documentation. Data analysis techniques through qualitative descriptives. Based on the results of data analysis that has been done, the results in the first cycle of learning motivation gained 81 with good interpretation increased in cycle II gained 94 with Very Good interpretation, this shows an increase of 13 points. To improve the learning process in Cycle I, it was scored 87 with Very Good Interpretation and in Cycle II to 95 with Very Good Interpretation showed an increase of 8 points, in Cycle I learning outcomes gained 71% mastery learning with Unfinished interpretation and in Cycle II increased to 89% with Completed Interpretation. Whereas when seen from the average value for cycle 1, it obtained a value of 74 with Good criteria and in cycle II it became 86.5 indicating an increase of 12.5 points. From this study, it can be concluded that the use of monopoly media in social studies subjects can improve motivation and learning outcomes Students in elementary schools